2001
DOI: 10.1128/jcm.39.1.228-234.2001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Infection Control Implications of Acinetobacter spp. in Hong Kong

Abstract: In a previous study, we showed that Acinetobacter genomic DNA group 3 was the most common species among blood culture isolates and was commonly found on superficial carriage sites of the healthy and the sick, which are different findings from those reported in Europe and North America. We used amplified ribosomal DNA restriction analysis and pulsed-field gel electrophoresis to study further the molecular epidemiology of acinetobacters in our region. Over a study period of 6 weeks with 136 consecutive routine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 44 publications
4
77
0
3
Order By: Relevance
“…Interestingly, A. baumannii and Acinetobacter genomic species 11 (each at 27%) were the predominant species, followed by A. calcoaceticus and Acinetobacter genomic species 3 (each at 13%), while Acinetobacter genomic species 13 was found only once. In Hong Kong, 51% of local vegetables were culture positive for Acinetobacter species, the majority of which were Acinetobacter genomic species 3 (75%), but one sample grew A. baumannii (245). Houang et al found acinetobacters in 22 of 60 soil samples in Hong Kong, and the most frequent species were Acinetobacter genomic species 3 (27%) and A. baumannii (23%), with only one sample yielding A. calcoaceticus (245).…”
Section: Natural Habitatsmentioning
confidence: 99%
“…Interestingly, A. baumannii and Acinetobacter genomic species 11 (each at 27%) were the predominant species, followed by A. calcoaceticus and Acinetobacter genomic species 3 (each at 13%), while Acinetobacter genomic species 13 was found only once. In Hong Kong, 51% of local vegetables were culture positive for Acinetobacter species, the majority of which were Acinetobacter genomic species 3 (75%), but one sample grew A. baumannii (245). Houang et al found acinetobacters in 22 of 60 soil samples in Hong Kong, and the most frequent species were Acinetobacter genomic species 3 (27%) and A. baumannii (23%), with only one sample yielding A. calcoaceticus (245).…”
Section: Natural Habitatsmentioning
confidence: 99%
“…Among members of the genus Acinetobacter baumannii species is most frequently isolated from humans [12,113,125]. These organisms are widely distributed in nature and may be present in soil, water and sewage, also are found in variety of foodstuffs [39,113,124].…”
Section: Introduction -Acinetobacter Baumanniimentioning
confidence: 99%
“…However, these MLST approaches cannot provide a real-time surveillance capability. Furthermore, Acinetobacter infections can be the result of one of several pathogenic Acinetobacter species, including A. baumannii, Acinetobacter genomospecies 13TU, or Acinetobacter genomospecies 3 (17,35,42,45).…”
mentioning
confidence: 99%